PEMBUATAN BARANG JADI KARET MENGGUNAKAN SULFUR - Rahmaniar Rahmaniar; Popy Marlina; Aprillena T.B (Balai Riset dan Standardisasi Industri Palembang, 2010)
The objective of the research was to obtain the rubber compound formulation with nano sulfur application in vulcanization process to produce vechicle rubber compound that will fulfill the standard specification. The experiment held by crushing the sulphr to covert intonano size through mechanical milling. Nano Sulphur were characterized with XRD method (X-RAY Difraction) and SEM method (Scanning Eletronical magnetic). The steps for making the rubber compound are mastication/milling the rubber and mixing with other supporting chemicals (activator, filler, softener, antioxidant, resin, accelerator) using the open mill, continued with vulcanization processwhich using nano sulphur as the vulcanization agent untilthe rubber compound ready to be molded.the experimental research used factorial completely randomized design with two factor as treatments, and each combination was replicated for three time. The first factor is the variation of vulcanization temperature (140 ˚C and 170˚C) and the second factor is the variation of suphur size (40nm,60nm,80nm, and 400nm). Tested parameters are modulus,elongation at break ,tear strength and density of rubber compound from the vehicle. The result showed that the variation of vulcanization elongation at break ,tear strength ,and density of rubber compound of the vehicle. The best treatment is obtained in temperature variation 140˚C and sulfur size 60nm (T1S2),with compound rubber characteristic of vehicle for modulus 108N/cm2,elongation at break 565% tear strength 90 kg/cm2, and density 1,220g/cm2.